Analisis Rencana Pelaksanaan Pembelajaran dalam Pembelajaran Menulis Narasi di SD - Windi Anggriani; Dian Indihadi (Program Studi PGSD UPI Kampus Tasikmalaya, 2018)
The learning implementation plan is a guide that teachers use to teach in the classroom. To be used as a reference in teaching. The learning implementation plan should always be prepared before the lesson begins. Each subject that will be taught the teacher to prepare the implementation plan of learning one of them in learning to write narration. This makes the researcher interested to know the implementation plan of learning narrative writing by paying attention to writing process. The purpose of this study is generally to describe the learning of narrative writing in the implementation plan of learning in primary school. The method used in this research is qualitative descriptive approach because the researcher want to get the description of the plan of the implementation of learning narrative writing in elementary school. This research was conducted at 12 elementary schools of Mitra Pendidikan Universitas Indonesia Tasikmalaya Campus which is SDN 2 Sukamaju, SDN 1 Nagarawangi, SDN Mugarsari, SDN 2 Sindangpalay, SDN Sukamenak Indah, SDN 2 Setiamulya, SDN Sukamulya, SDN Karangsambung, SDN Pahlawan, SDN Mangkubumi, SDN Gunungpereng, SDN Sambongpermai in tasikmalaya city with the subject of research plan of learning implementation in class V. Data collection techniques used in the form of observation and study of the documentation. Based on the results of data analysis obtained from the implementation plan of learning narrative writing by using the process of narration in class V is still low. This is seen five indicators studied are only three indicators that often appear. The most indicators appear in the selection indicators and the main ideas to describe topics based on themes, the correction of the writing framework, the writing of the blur (draft) in accordance with the contents of the writing based on the completeness of language, while the rarely indicator indicator of topic determination narrative based on themes and improvements ( Perevisian) errors of writing results based on the findings of errors in outlining ideas based on the draft that has been madeRencana pelaksanaan pembelajaran adalah suatu pedoman yang digunakan guru untuk mengajar dikelas. Untuk dijadikan acuan dalam mengajar. Rencana pelaksanaan pembelajaran harus selalu disiapkan sebelum pembelajaran dimulai. Setiap mata pelajaran yang akan diajarkan guru mempersiapkan rencana pelaksanaan pembelajaran salah satunya dalam pembelajaran menulis narasi. Hal ini menjadikan peneliti tertarik untuk mengetahui rencana pelaksanaan pembelajaran menulis narasi dengan memperhatikan proses menulis. tujuan dari penelitian ini secara umum untuk mendeskripsikan pembelajaran menulis narasi dalam rencana pelaksanaan pembelajaran di sekolah dasar. Metode yang digunakan dalam penelitian ini adalah pendekatan deskriptif kualitatif karena peneliti ingin mendapatkan gambaran rencana pelaksanaan pembelajaran menulis narasi di sekolah dasar. Penelitian ini dilaksanakan di 12 Sekolah Dasar Mitra Universitas Pendidikan Indonesia Kampus Tasikmalaya yaitu SDN 2 Sukamaju, SDN 1 Nagarawangi, SDN Mugarsari, SDN 2 Sindangpalay, SDN Sukamenak Indah, SDN 2 Setiamulya, SDN Sukamulya, SDN Karangsambung, SDN Pahlawan, SDN Mangkubumi, SDN Gunungpereng, SDN Sambongpermai di kota tasikmalaya dengan subjek penelitian rencana pelaksanaan pembelajaran di kelas V. Teknik pengumpulan data yang digunakan berupa observasi dan studi dokementasi. Berdasarkan hasil analisis data yang diperoleh dari rencana pelaksanaan pembelajaran menulis narasi dengan menggunakan proses narasi di kelas V masih rendah. Hal ini terlihat lima indikator yang diteliti hanya tiga indikator yang sering muncul. Indikator paling banyak muncul pada indikator pemilihan dan penyusunan gagasan utama untuk mendeskripsikan topik berdasarkan tema, pengoreksian kerangka tulisan, penulisan buram (draf) sesuai kerangka isi tulisan berdasarkan kelengkapan kebahasaan, sedangkan indikator yang jarang muncul yaitu indikator penentuan topik karangan narasi berdasarkan tema dan perbaikan (perevisian) kesalahan hasil tulisan berdasarkan temuan kesalahan dalam menjabarkan ide gagasan berdasarkan draf yang telah dibuat.